2019
DOI: 10.1016/j.ebiom.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells from patients with cirrhosis display a phenotype that may contribute to cirrhosis-associated immune dysfunction

Abstract: a b s t r a c tBackground: Cirrhosis-associated immune dysfunction (CAID) contributes to high sepsis risk in patients with chronic liver disease. Various innate and; to a lesser extent; adaptive immune dysfunctions have been described as contributors to CAID leading to immune-paresis and impaired anti-microbial response in cirrhosis. In this study, we examined the phenotype of CD8 + T cells in chronic liver disease with the aim to evaluate changes that might contribute to impaired immune responses. Methods: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 27 publications
6
54
0
2
Order By: Relevance
“…These findings are consistent with previous reports that show increased expression of MERTK + monocytes in acute-on-chronic-liver disease patients that display impaired pro-inflammatory cytokine production correlating with disease severity [10]. The importance of an inflammatory microenvironment in driving the predominant HLA-DR + CD8 + T cell phenotype in cirrhosis was demonstrated in this study; the inflammatory milieu of cirrhosis contributes to this phenotype in suppressing the immune system and rendering individuals more susceptible to infections [8].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous reports that show increased expression of MERTK + monocytes in acute-on-chronic-liver disease patients that display impaired pro-inflammatory cytokine production correlating with disease severity [10]. The importance of an inflammatory microenvironment in driving the predominant HLA-DR + CD8 + T cell phenotype in cirrhosis was demonstrated in this study; the inflammatory milieu of cirrhosis contributes to this phenotype in suppressing the immune system and rendering individuals more susceptible to infections [8].…”
supporting
confidence: 93%
“…The innate immune dysfunctions of CAID are well described, however, to date the adaptive immune abnormalities in cirrhotic patients have only partially been explored. In an article in EBioMedicine , Lebossé and colleagues studied CD8 + T cells in patients with cirrhosis and for the first time, report the presence of an activated dysfunctional subset that may impact susceptibility to infection and correlate with poor disease outcome [8]. The authors demonstrate the expansion of an immunosuppressive HLA-DR expressing CD8 + T cell subset, not only in circulation but also in peritoneal and intrahepatic compartments; an association was evident for this expanded immunosuppressive immune subset with development of infection.…”
mentioning
confidence: 99%
“…Bacterial infections occur frequently in cirrhotic patients (32-34%) (51,52) and are the main precipitant for hepatic acute decompensation (AD) without and with organ failure [acute-on-chronic liver failure (ACLF)] (53,54). Similarly to ALF (3), cirrhosis and ACLF are associated with inflammation and, as disease progresses, immune dysfunction that contribute to increased infection susceptibility (5,8,(55)(56)(57). It would be important to further investigate the significance of the PD-1/PD-L1 pathway in cirrhosis, AD and ACLF and its contribution to systemic and hepatic immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enrichment of co‐regulatory receptor expression maybe a mere physiological response to the liver microenvironment and not necessarily of a failing immune response in disease 19 . Owusu Sekyere et al, 19 and independently Lebossé et al 37 in cirrhotic patients only, have demonstrated that soluble mediators (elevated or decreased cytokines and other inflammatory mediators) contribute to the elevated expression of co‐regulatory molecules in virus‐specific CD8 + T cells. Further studies are needed to elucidate the precise soluble factors underpinning this induction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enrichment of co-regulatory receptor expression maybe a mere physiological response to the liver microenvironment and not necessarily of a failing immune response in disease. 19 Owusu Sekyere et al, 19 and independently Lebossé et al 37 Cell exhaustion is also designated as a loss of CD8 + T-cell function, for example proliferation and cytokine secretion, and it has been reported by several groups. 11,[38][39][40] Our results concerning the HCV- Interestingly, our analyses regarding cytokine production for HCV, CMV-and Flu-specific CD8 + T cells are in agreement with results of other studies confirming the abundance of later memory cells (ie M2 and M3 subsets of memory cells) within these Ag-specific populations.…”
Section: F I G U R Ementioning
confidence: 99%